Natural surfactant for sustainable carbon utilization in cleaner production of fossil fuels: Extraction, characterization and application studies. Issue 5 (October 2021) - Singh, Alpana; Chaturvedi, Krishna Raghav; Sharma, Tushar
Abstract: In this study, the extraction, characterization, and performance evaluation of a green surfactant, derived from bio-resource (Fenugreek seeds), is reported for effective carbon utilization in subsurface applications. Several characterization tools such as Fourier-transform infrared spectroscope, ultraviolet–visible spectroscope, methylene blue active substance test, surface tension tests, and scanning electron microscope were used to confirm saponin (surface activity) in synthesized surfactant and suitably compared with the properties of conventional surfactants in literature. The prepared green surfactant exhibited anionic behavior as validated by elemental analysis and adsorption studies. The critical micellar concentration of surfactant was determined by surface tension and electrical conductivity and its value was found to be around 0.2 wt%. Carbon dioxide absorption potential of green surfactant was envisaged by molality tests which confirmed that carbon dioxide absorption rate of surfactant was 7–18% higher than pure water. As a result, the surfactant showed high foam volume (> 40 ml) and foaming stability (8–10 h). The high temperature performance was also better. At 90 °C, carbon dioxide bubbles of larger size were present in sufficient quantity which indicated that foaming potential of surfactant was not severely affected by temperature. During adsorption studies, the green surfactant solution showed a mass-loss of 48–60% on a sandstone surface, which is better than the one of a conventional surfactant. It also showed superior property than conventional surfactants in adsorption isotherm investigations. Thus, the use of these green surfactants in subsurface scenario for carbon utilization and oil recovery from a porous media is recommended. Graphical Abstract: Synthesis of green surfactant from bio-resource and its utilization in effective carbon sequestration. ga1 Highlights: Green surfactant is derived from bio resource using a cheap and efficient process. Micelle formation achieved at low concentration (≤ 0.2 wt%), in line with past studies. CO2 absorption capacity of green surfactant was 9–15% higher than water. Green surfactant solutions showed superior foaming with CO2 foams stable at 90 °C. Proposal of using green surfactant solutions in CO2 sequestration applications.